Melhores políticas para melhores vidas: um estudo crítico das concepções que embasam o Programme For International Student Assessment (PISA) no período 1997-2012 - Libanori, Guilherme Andolfatto (2015)
This work has as its object of study the Programme For International Student Assessment (PISA), an international assessment system, created in 1997 by the Organization for Economic Co-operation and Development (OECD) and reaches fifteen students who are in final phase of compulsory schooling. The objective of this study is to analyze the PISA through its justification of creation, objectives and concepts that underlie the official documents of the OECD. In particular, through the analysis of conceptions of quality, equity and accountability in official documents of PISA, we seek to understand to what extent these conceptions are articulated with the economic development goals of OECD, as well as understand the participation of the Organization in educational policies, identify practices that the discourse of OECD seeks to engender in education management and how these conceptions allow to legitimate new forms of assessment which gradually reorganize and impose a new form to the educational process schooled. The theoretical-methodological approach is based on bibliographic and documentary research. The analysis will take place by means of the categories of discursive and social practices, by Paul Veyne, modernization and rationalization, by Max Weber, and the conceptions of social justice and equity, by John Rawls. Our analyzes showed that PISA is a producer and promoter of discursive practices, which aims to spread the instrumental rationality in education, standardize knowledge and skills required by the economic sphere, as well as homogenize and optimize the educational policies worldwide. Thus, PISA is more than an evaluation system, it is a global governance agent that, which through indications and discursive persuasion, kind of soft power actions made by the OECD and legitimized by the participating countries, seeks to disseminate best economic practices in order to homogenize the international productive sphere. Therefore, PISA is projected as an education regulation tool for economic and political purposes.